RESPON PEROKOK AKTIF TENTANG PESAN BAHAYA MEROKOK DALAM KEMASAN ROKOK YANG DILAKUKAN PADA MAHASISWA UNIVERSITAS ISLAM MAJAPAHIT MOJOKERTO FAKULTAS TEKNIK - Dwiharini Puspitaningsih, S.Kep.,Ns.,M.Kep; Nur Rahmawati Febrianti A.P (Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2021)
Most smokers do adolescents in which teens are aged 18-25 years where at that age as a productive age, giving photographs on cigarette packages is expected to make consumers think repeatedly before deciding to smoke. this study aimed to determine the Active Smoker Response About the Dangerous Message of Smoking in Cigarette Packaging Conducted on Students Colloge. This study used a descriptive method, and purposive sampling technique with 28 respondents Students of the Faculty of Engineering Majapahit Islamic University Mojokerto, which are observed according to inclusion criteria, and respondent responses more deeply by observation used a respoon questionnaire, distributing questionnaires online used the Google Form which is done in one time only.The results of this studied is the affective response research are in the first place,which is means altought the respondent’s knowledge about the dangerous of smoking message image on cigarette packs and the respondent’s emotions towards the sentence and the message about the dangers of smoking is quite good, this is not a benchmark for respondent’s to leave the smoking habit or reduce the habits of smoke.